2016
DOI: 10.1177/2329496516663225
|View full text |Cite
|
Sign up to set email alerts
|

Tactics and Targets: Explaining Shifts in Grassroots Environmental Resistance

Abstract: Corporate misconduct is often associated with environmental, political, and social problems, and the effects are often felt at the local level where disenfranchised residents may have less access to political power. We know that grassroots movements can take various tactical paths as they challenge elites, yet we aim to map the specific pathways that lead to shifts in tactical repertoires, especially as groups transition to increasingly confrontational tactics. Drawing from social movement theory on tactics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…At the individual level, such behaviors encompass environmental risk avoidance (O’Neill 2003) and may include restricting time outdoors, using indoor air purifiers, and taking other precautions to avoid health risks associated with pollution. At the collective level, communities may pressure political and corporate institutions to engage in risk reduction, primarily via remediation or relocation (Adams and Shriver 2017; Buday 2017; Čapek 1993).…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, such behaviors encompass environmental risk avoidance (O’Neill 2003) and may include restricting time outdoors, using indoor air purifiers, and taking other precautions to avoid health risks associated with pollution. At the collective level, communities may pressure political and corporate institutions to engage in risk reduction, primarily via remediation or relocation (Adams and Shriver 2017; Buday 2017; Čapek 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies on conflicts between local community and companies have been widely carried out. The main issues discussed in the study included land use seizure, declination of mine development plans, exposure to mining wastes that threatened local communities and demands for post-mining recovery [4], [5], [9], [12]. The majority of study's findings examine the issue of land ownership seizure and exposure to mining waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conflict studies between local communities and companies focus on local communities effort to fight for their interests [4], [5], the government as a mediator in suppressing escalation of conflict through companies power [9], Non-Government Organization (NGO) as a mediator and community facilitator [13]. The study of Adams and Shriver (2017) on the local community strategy in paying compensation for the pollution by the company is crucial in this article as they equally focused on the local community tactics in dealing with the companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In their research on an industrial town polluted by an oil refinery, Adams et al . () found that residents reporting health problems were subjected to threats and intimidation from those supporting the facility. Similarly, workers at the U.S. Government's Oak Ridge Nuclear facility were subjected to job loss and demotions, retaliation, and on‐the‐job harassment when they spoke out about environmental health concerns (Cable et al .…”
Section: Sociology Of Diagnosismentioning
confidence: 99%